Aqueous Polymerization of Divinyl Monomers Initiated by Mn(III)-Amino Acid Chelating Agents - Sivakumar, G.; Krishnaveni, N.; Umayavalli, M.; Gopalkrishnan (Asian Journal of Chemistry, 2012)
The polymerization kinetics of N,N'-methylenebisacrylamide initiated by the redox pairs trisacetatomanganese(III) dehydrate-ethylenediaminetetracetic acid and trisacetatomanganese(III) dehydrate - nitrilotriacetic acid in dilute sulphuric acid medium was investigated. The rate of polymerization Rp, was proportional to [MBA]1.1, [EDTA]0.4 and inverse dependence to [Mn(III)] for MBA-Mn(III)-EDTA system and [MBA]1.1, [NTA]0.7 and inverse dependence to [Mn(III)] for MBA-Mn(III)-NTA system. The rate of manganic ion disappearance Rm, was directly proportional to [Mn(III)] and [Red] but independent of monomer for both the systems. Both Rp and Rm were not affected by the changes in [H+], ionic strength, added Mn(II) and Rp decreased with the addition of sodium nitrate. The activation energy was evaluated by using Arrhenius plot. Suitable mechanism has been proposed to explain the observed kinetic data.